A method for preparing a cooling film for a greenhouse

By amidizing the nano-aluminum powder and other materials and preparing cooling masterbatches, a five-layer structure cooling greenhouse film was prepared, which solved the problems of unsatisfactory results and high costs in existing greenhouses, and achieved significant cooling and permeability. Good light uniformity effect.

CN119189380BActive Publication Date: 2025-02-25青州市鲁冠塑料有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411726846.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing greenhouse cooling measures have problems such as unsatisfactory cooling effects, high cost, short film life and poor light transmission uniformity.

Method used

By mixing nano-aluminum powder, nano-alumina powder, neodymium sulfate, and cesium tungstate, amidation modification, and cooling masterbatches are prepared, and a five-layer structure cooling shed film is finally prepared.

Benefits of technology

It achieves significant cooling without reducing the film intensity, and ensures the uniformity of the film's light transmittance and ultraviolet infrared barrier rate in different parts, ensuring uniform growth of crops.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a method for preparing a cooling greenhouse film that can be used in a greenhouse, and belongs to the field of polymer compositions. The preparation method comprises mixed calcination, amidation modification, preparation of cooling masterbatch, and preparation of cooling greenhouse film. The cooling greenhouse film prepared by the invention has good uniformity of optical properties, wherein the uniformity of light transmission is 0.08-0.11%, the uniformity of infrared blocking is 0.15-0.17%, and the uniformity of ultraviolet blocking is 0.09-0.12%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a temperature-reducing greenhouse film which can be used for a greenhouse, and belongs to the field of polymer compositions. Background Art

[0002] In summer, solar radiation is strong and the light intensity is higher than the light saturation point of plants. The excess light energy cannot be used for photosynthesis of crops. Not only will it fail to increase yields, but it will cause strong light stress to crops, posing a serious threat to the growth of greenhouse vegetables, causing sunburn to fruits, flowers and leaves, and affecting product quality.

[0003] Currently common cooling measures include covering with shade nets, applying mud, spraying cooling agents, etc. Among them, the shade nets absorb a lot of heat and will directly transfer the heat to the greenhouse film, shortening the life of the greenhouse film. At the same time, the heat dissipation in the greenhouse is slow due to the tight coverage, and the ideal cooling effect cannot be achieved. Applying mud is more laborious, and it will be washed away by rain when it rains, and the cooling effect will be lost. Spraying cooling agents on the greenhouse film can make the greenhouse film achieve a better cooling effect, and because the greenhouse film is covered with a layer of coating, the firmness of the greenhouse film will be increased, but it will affect the light transmittance of the film, and with the extension of time, the life of the greenhouse film will be reduced and it will become brittle.

[0004] In the prior art, there is a polymer film with a surface structure of silver and silicon oxide coatings, which achieves a cooling effect by reflecting light to reduce the temperature on one side of the film. The cooling performance is relatively excellent, but the thickness of the coating itself is measured in microns, which is not high. This leads to damage to the coating through friction during daily use, thereby destroying the cooling effect of the film. In addition, the price of preparing the silver coating is relatively expensive, resulting in a high cost of the film.

[0005] CN114133648A discloses a reflective diffuse scattering greenhouse film and a preparation method thereof. A certain proportion of aluminum powder and mica powder are added to the middle layer to generate silver spots inside the greenhouse film to reflect and scatter light, which can reduce the light transmittance and scatter the transmitted light. The greenhouse film reduces the light transmittance by reflecting light instead of absorbing light, which can significantly extend the service life of the greenhouse film and play a cooling role. Adding a medium that can reflect sunlight to the middle layer can avoid the disadvantage that the surface coating is easily damaged, but the disadvantages of this film are also very obvious. Untreated aluminum powder and mica powder, after being dispersed in the film, will cause the film to have poor light transmittance uniformity and reflection uniformity. Even if the physical distribution of aluminum powder and mica powder in the film is relatively uniform, the reflectivity and light transmittance of the film at different positions are also quite different, which in turn affects the cooling effect of the film and causes differences in the growth state during the growth of crops. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defects of the prior art. Nano aluminum powder, nano alumina powder, neodymium sulfate and cesium tungstate are mixed and calcined, amidated and modified, and prepared as cooling masterbatch, and finally as cooling greenhouse film. Without reducing the strength of the film, a more obvious cooling effect is achieved. At the same time, the transmittance and ultraviolet infrared blocking rate of the film at different parts are uniform, thereby ensuring uniform growth of crops.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A method for preparing a cooling greenhouse film that can be used in a greenhouse comprises mixing and calcining, amidation modification, preparing a cooling masterbatch, and preparing the cooling greenhouse film.

[0009] The following are further improvements to the above technical solution:

[0010] The mixed calcination method comprises: mixing nano aluminum powder, nano alumina powder, neodymium sulfate and cesium tungstate in a mixer to obtain a mixed powder; then controlling the temperature to be 1300-1400° C., calcining the mixed powder in a nitrogen atmosphere for 85-100 minutes; and obtaining a calcined mixed powder after the calcination is completed;

[0011] The mass ratio of the nano aluminum powder, nano alumina powder, neodymium sulfate and cesium tungstate is 175-225:70-80:2.5-3.5:20-30;

[0012] The particle size of the nano aluminum powder is 55 nm;

[0013] The nano alumina powder is β-alumina with a particle size of 147 nm.

[0014] The amidation modification method comprises: mixing the calcined mixed powder with an ethylenediaminetetraacetic acid solution, soaking the mixed powder at room temperature for 25-35 minutes, filtering, washing and drying the mixed powder under a nitrogen atmosphere after the soaking is completed to obtain an acid-treated mixed powder, mixing the acid-treated mixed powder with N,N-dimethylformamide, stirring to make it dispersed evenly, then adding diethylenetriamine, stirring to make it completely dissolved, then adding carbodiimide, controlling the temperature to 77-79° C., stirring for 185-210 minutes, filtering, washing and drying the mixed powder under a nitrogen atmosphere after the stirring is completed, and redispersing the mixed powder to a particle size of less than 150 nm to obtain an amidation-modified mixed powder;

[0015] The mass ratio of the calcined mixed powder to the ethylenediaminetetraacetic acid solution is 10:70-80;

[0016] The concentration of the ethylenediaminetetraacetic acid solution is 0.8-1.1 mol / L;

[0017] The mass ratio of the acid-treated mixed powder, N,N-dimethylformamide, diethylenetriamine and carbodiimide is 45-55:525-625:70-80:0.9-1.1.

[0018] The method for preparing the cooling masterbatch is as follows: feeding the amidation modified mixed powder and the fumed silica powder into a mixer, adding linear low-density polyethylene, an antioxidant, and a light stabilizer after mixing evenly, controlling the temperature to be 172-178° C., mixing for 55-65 minutes, and after the mixing is completed, extruding and granulating to obtain the cooling masterbatch;

[0019] The mass ratio of the amidated modified mixed powder, fumed silica powder, linear low-density polyethylene, antioxidant, and light stabilizer is 13-16:4.5-5.5:175-195:0.9-1.1:0.9-1.1;

[0020] The particle size of the fumed silica powder is 40 nm;

[0021] The density of the linear low-density polyethylene is 0.933 g / cm 3 ;

[0022] The model of the antioxidant is antioxidant 168;

[0023] The light stabilizer is a hindered amine stabilizer, and the model is light stabilizer 944.

[0024] The method for preparing the cooling greenhouse film comprises: uniformly mixing an outer layer material, a sub-outer layer material, a middle layer material, a sub-inner layer material, and an inner layer material, respectively, adding the materials to five extruders corresponding to the outer layer, the sub-outer layer, the middle layer, the sub-inner layer, and the inner layer, respectively, setting the extrusion working temperature of the five extruders to 177-182° C., sequentially performing melting, mixing, and plasticizing, and then extruding the plasticized materials in the five extruders into the die head of the same five-layer co-extrusion film blowing machine for fusion, and extruding the materials through the die mouth in a tubular shape, and then performing blow molding, cooling, and winding to obtain the cooling greenhouse film;

[0025] The structure of the cooling greenhouse film is an outer layer, a sub-outer layer, a middle layer, a sub-inner layer, and an inner layer from top to bottom. The thickness of the outer layer is 0.03mm, the thickness of the sub-outer layer is 0.025mm, the thickness of the middle layer is 0.04mm, the thickness of the sub-inner layer is 0.025mm, the thickness of the inner layer is 0.03mm, and the total thickness of the cooling greenhouse film is 0.15mm.

[0026] The outer layer material comprises the following components by weight: 14-16 parts of low-density polyethylene, 45-55 parts of metallocene polyethylene, 32-38 parts of linear low-density polyethylene, 0.7-0.9 parts of antioxidant, 0.7-0.9 parts of light stabilizer, and 0.45-0.55 parts of antioxidant;

[0027] The secondary outer layer material comprises the following components by weight: 23-27 parts of low-density polyethylene, 42-48 parts of metallocene polyethylene, 14.5-15.5 parts of linear low-density polyethylene, 4.5-5.5 parts of cooling masterbatch, and 0.45-0.55 parts of antioxidant;

[0028] The middle layer material comprises the following components by weight: 23-27 parts of low-density polyethylene, 42-48 parts of metallocene polyethylene, 14.5-15.5 parts of linear low-density polyethylene, 0.8-1.2 parts of fumed silica powder, and 0.45-0.55 parts of antioxidant;

[0029] The secondary inner layer material comprises the following components by weight: 23-27 parts of low-density polyethylene, 42-48 parts of metallocene polyethylene, 14.5-15.5 parts of linear low-density polyethylene, 4.5-5.5 parts of cooling masterbatch, and 0.45-0.55 parts of antioxidant;

[0030] The inner layer material comprises the following components by weight: 14-16 parts of low-density polyethylene, 45-55 parts of metallocene polyethylene, 32-38 parts of linear low-density polyethylene, 0.7-0.9 parts of antioxidant, 0.7-0.9 parts of light stabilizer, and 0.45-0.55 parts of antioxidant;

[0031] The particle size of the fumed silicon dioxide powder in the middle layer material is 40 nm;

[0032] The density of the low-density polyethylene in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is 0.920 g / cm 3 The density of metallocene polyethylene is 0.927 g / cm 3 The density of linear low-density polyethylene is 0.933 g / cm 3 ;

[0033] The antioxidant model in the outer layer material, sub-outer layer material, middle layer material, sub-inner layer material and inner layer material is antioxidant 4010NA; the light stabilizer hindered amine stabilizer in the outer layer material and inner layer material is light stabilizer 944; the antioxidant in the outer layer material and inner layer material is antioxidant 168.

[0034] Compared with the prior art, the present invention achieves the following beneficial effects:

[0035] The cooling greenhouse film prepared by the present invention has excellent physical properties. According to the method in GB / T1040.1-2006, the transverse tensile strength, longitudinal tensile strength, transverse elongation at break and longitudinal elongation at break of the film are tested. The transverse tensile strength is 32.55-33.11 MPa, the longitudinal tensile strength is 32.81-33.24 MPa, the transverse elongation at break is 952.4-962.1%, and the longitudinal elongation at break is 875.5-882.3%; according to GB / T16578.2-2009, the Elmendorf method is used to test the transverse right-angle tear load and longitudinal right-angle tear load of the film. The transverse right-angle tear load is 28.17-28.52 KN / m, and the longitudinal right-angle tear load is 22.38-23.04 KN / m; according to the method in GB / T9639.1-2008, the dart drop impact strength of the film is tested, and the dart drop impact strength is 942-975 g;

[0036] The cooling greenhouse film prepared by the present invention has good cooling performance. When the external temperature is high, the inner side of the film can maintain a low temperature. The cooling film is placed in a closed container, and the two sides of the film are completely isolated. The inner layer side and the outer layer side are completely sealed independent spaces, and the outer layer side of the greenhouse film is irradiated with simulated sunlight with an intensity of 100000LUX. During irradiation, the temperature of the environment on the outer layer side is controlled to be 45°C, and the temperature on the inner layer side is controlled to be room temperature 23°C. The outer layer side of the film is continuously irradiated, and the temperature of the inner layer side is detected at 0h, 2h, 6h, and 12h of irradiation. The temperature of the inner layer side at 0h is 25.2°C, the temperature of the inner layer side after continuous irradiation for 2h is 26.8-27.1°C, the temperature of the inner layer side after continuous irradiation for 6h is 28.0-28.3°C, and the temperature of the inner layer side after continuous irradiation for 12h is 30.3-30.7°C.

[0037] The cooling greenhouse film prepared by the present invention has excellent optical properties. When tested using an ultraviolet infrared blocking rate and a visible light transmittance tester, the average infrared blocking rate of the film is 45.6-46.1%, the average ultraviolet blocking rate is 95.2-95.4%, and the average light transmittance is 91.7-92.1%.

[0038] The cooling greenhouse film prepared by the present invention has good uniformity of optical properties. In a 1000mm×1000mm sample, each area unit of 100mm×100mm is taken as a test unit, 100 test units are tested for each sample, and the extreme values ​​of the highest and lowest two test unit values ​​in each sample are taken as uniformity indicators, among which the light transmittance uniformity is 0.08-0.11%, the infrared blocking uniformity is 0.15-0.17%, and the ultraviolet blocking uniformity is 0.09-0.12%. DETAILED DESCRIPTION Example 1

[0039] (1) Mixed calcination

[0040] Nano aluminum powder, nano alumina powder, neodymium sulfate and cesium tungstate are uniformly mixed in a mixer to obtain a mixed powder, and then the temperature is controlled to be 1350° C., and the mixed powder is calcined in a nitrogen atmosphere for 90 minutes. After the calcination is completed, a calcined mixed powder is obtained;

[0041] The mass ratio of the nano aluminum powder, nano alumina powder, neodymium sulfate and cesium tungstate is 200:75:3:25;

[0042] The particle size of the nano aluminum powder is 55 nm;

[0043] The nano alumina powder is β-alumina with a particle size of 147 nm.

[0044] (2) Amidation modification

[0045] The calcined mixed powder is mixed with ethylenediaminetetraacetic acid solution, and soaked at room temperature for 30 minutes. After the soaking is completed, it is filtered, washed, and dried in a nitrogen atmosphere to obtain an acid-treated mixed powder. The acid-treated mixed powder is mixed with N,N-dimethylformamide, stirred to be evenly dispersed, and then diethylenetriamine is added and stirred to be completely dissolved. Then, carbodiimide is added, the temperature is controlled to 78°C, and stirred for 200 minutes. After the stirring is completed, it is filtered, washed, and dried in a nitrogen atmosphere, and redispersed to a particle size of less than 150 nm to obtain an amidated modified mixed powder;

[0046] The mass ratio of the calcined mixed powder to the ethylenediaminetetraacetic acid solution is 10:75;

[0047] The concentration of the ethylenediaminetetraacetic acid solution is 1 mol / L;

[0048] The mass ratio of the acid-treated mixed powder, N,N-dimethylformamide, diethylenetriamine and carbodiimide is 50:600:75:1.

[0049] (3) Preparation of cooling masterbatch

[0050] The amidated modified mixed powder and fumed silica powder were fed into a mixer, and after being evenly mixed, linear low-density polyethylene, antioxidant and light stabilizer were added. The temperature was controlled at 174°C and the mixing was carried out for 60 minutes. After the mixing was completed, the mixture was extruded and granulated to obtain a cooling masterbatch.

[0051] The mass ratio of the amidated modified mixed powder, fumed silica powder, linear low-density polyethylene, antioxidant, and light stabilizer is 15:5:185:1:1;

[0052] The particle size of the fumed silica powder is 40 nm;

[0053] The density of the linear low-density polyethylene is 0.933 g / cm 3 ;

[0054] The model of the antioxidant is antioxidant 168;

[0055] The light stabilizer is a hindered amine stabilizer, and the model is light stabilizer 944.

[0056] (4) Preparation of cooling greenhouse film

[0057] The outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material are mixed evenly respectively, and added into five extruders corresponding to the outer layer, the sub-outer layer, the middle layer, the sub-inner layer and the inner layer respectively, and the extrusion working temperature of the five extruders is set to 180° C., and melting, mixing and plasticizing are performed in sequence, and then the plasticized materials in the five extruders are squeezed into the die head of the same five-layer co-extrusion film blowing machine for fusion, and extruded in a tubular shape through the die mouth, and then blown, cooled and rolled to obtain a cooling shed film;

[0058] The structure of the cooling greenhouse film is an outer layer, a sub-outer layer, a middle layer, a sub-inner layer, and an inner layer from top to bottom. The thickness of the outer layer is 0.03mm, the thickness of the sub-outer layer is 0.025mm, the thickness of the middle layer is 0.04mm, the thickness of the sub-inner layer is 0.025mm, the thickness of the inner layer is 0.03mm, and the total thickness of the cooling greenhouse film is 0.15mm.

[0059] The outer layer material comprises the following components by weight: 15 parts of low-density polyethylene, 50 parts of metallocene polyethylene, 35 parts of linear low-density polyethylene, 0.8 parts of antioxidant, 0.8 parts of light stabilizer, and 0.5 parts of antioxidant;

[0060] The secondary outer layer material comprises the following components by weight: 25 parts of low-density polyethylene, 45 parts of metallocene polyethylene, 15 parts of linear low-density polyethylene, 5 parts of cooling masterbatch, and 0.5 parts of antioxidant;

[0061] The middle layer material comprises the following components by weight: 25 parts of low-density polyethylene, 45 parts of metallocene polyethylene, 15 parts of linear low-density polyethylene, 1 part of fumed silica powder, and 0.5 parts of antioxidant;

[0062] The secondary inner layer material comprises the following components by weight: 25 parts of low-density polyethylene, 45 parts of metallocene polyethylene, 15 parts of linear low-density polyethylene, 5 parts of cooling masterbatch, and 0.5 parts of antioxidant;

[0063] The inner layer material comprises the following components by weight: 15 parts of low-density polyethylene, 50 parts of metallocene polyethylene, 35 parts of linear low-density polyethylene, 0.8 parts of antioxidant, 0.8 parts of light stabilizer, and 0.5 parts of antioxidant;

[0064] The particle size of the fumed silicon dioxide powder in the middle layer material is 40 nm;

[0065] The density of the low-density polyethylene in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is 0.920 g / cm 3 The density of metallocene polyethylene is 0.927 g / cm 3 The density of linear low-density polyethylene is 0.933 g / cm 3 ;

[0066] The antioxidant model in the outer layer material, sub-outer layer material, middle layer material, sub-inner layer material and inner layer material is antioxidant 4010NA; the light stabilizer hindered amine stabilizer in the outer layer material and inner layer material is light stabilizer 944; the antioxidant in the outer layer material and inner layer material is antioxidant 168.

[0067] Example 2

[0068] (1) Mixed calcination

[0069] The nano aluminum powder, nano alumina powder, neodymium sulfate and cesium tungstate are uniformly mixed in a mixer to obtain a mixed powder, and then the temperature is controlled to be 1300° C., and the mixed powder is calcined in a nitrogen atmosphere for 100 minutes. After the calcination is completed, a calcined mixed powder is obtained;

[0070] The mass ratio of the nano aluminum powder, nano alumina powder, neodymium sulfate and cesium tungstate is 175:70:2.5:20;

[0071] The particle size of the nano aluminum powder is 55 nm;

[0072] The nano alumina powder is β-alumina with a particle size of 147 nm.

[0073] (2) Amidation modification

[0074] The calcined mixed powder is mixed with ethylenediaminetetraacetic acid solution, and soaked at room temperature for 25 minutes. After the soaking is completed, it is filtered, washed, and dried in a nitrogen atmosphere to obtain an acid-treated mixed powder. The acid-treated mixed powder is mixed with N,N-dimethylformamide, stirred to be evenly dispersed, and then diethylenetriamine is added and stirred to be completely dissolved. Then, carbodiimide is added, the temperature is controlled to 77°C, and stirred for 210 minutes. After the stirring is completed, it is filtered, washed, and dried in a nitrogen atmosphere, and redispersed to a particle size of less than 150 nm to obtain an amidated modified mixed powder;

[0075] The mass ratio of the calcined mixed powder to the ethylenediaminetetraacetic acid solution is 10:70;

[0076] The concentration of the ethylenediaminetetraacetic acid solution is 1.1 mol / L;

[0077] The mass ratio of the acid-treated mixed powder, N,N-dimethylformamide, diethylenetriamine and carbodiimide is 45:525:70:0.9.

[0078] (3) Preparation of cooling masterbatch

[0079] The amidated modified mixed powder and fumed silica powder were fed into a mixer, and after being evenly mixed, linear low-density polyethylene, antioxidant and light stabilizer were added. The temperature was controlled at 172°C and the mixing time was 65 minutes. After the mixing was completed, the mixture was extruded and granulated to obtain a cooling masterbatch.

[0080] The mass ratio of the amidated modified mixed powder, fumed silica powder, linear low-density polyethylene, antioxidant, and light stabilizer is 13:4.5:175:0.9:0.9;

[0081] The particle size of the fumed silica powder is 40 nm;

[0082] The density of the linear low-density polyethylene is 0.933 g / cm 3 ;

[0083] The model of the antioxidant is antioxidant 168;

[0084] The light stabilizer is a hindered amine stabilizer, and the model is light stabilizer 944.

[0085] (4) Preparation of cooling greenhouse film

[0086] The outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material are mixed evenly respectively, and added into five extruders corresponding to the outer layer, the sub-outer layer, the middle layer, the sub-inner layer and the inner layer respectively, and the extrusion working temperature of the five extruders is set to 177°C, and melting, mixing and plasticizing are performed in sequence, and then the plasticized materials in the five extruders are squeezed into the die head of the same five-layer co-extrusion film blowing machine for fusion, and extruded in a tubular shape through the die mouth, and then blown, cooled and rolled to obtain a cooling greenhouse film;

[0087] The structure of the cooling greenhouse film is an outer layer, a sub-outer layer, a middle layer, a sub-inner layer, and an inner layer from top to bottom. The thickness of the outer layer is 0.03mm, the thickness of the sub-outer layer is 0.025mm, the thickness of the middle layer is 0.04mm, the thickness of the sub-inner layer is 0.025mm, the thickness of the inner layer is 0.03mm, and the total thickness of the cooling greenhouse film is 0.15mm.

[0088] The outer layer material comprises the following components by weight: 14 parts of low-density polyethylene, 45 parts of metallocene polyethylene, 32 parts of linear low-density polyethylene, 0.7 parts of antioxidant, 0.7 parts of light stabilizer, and 0.45 parts of antioxidant;

[0089] The secondary outer layer material comprises the following components by weight: 23 parts of low-density polyethylene, 42 parts of metallocene polyethylene, 14.5 parts of linear low-density polyethylene, 4.5 parts of cooling masterbatch, and 0.45 parts of antioxidant;

[0090] The middle layer material comprises the following components by weight: 23 parts of low-density polyethylene, 42 parts of metallocene polyethylene, 14.5 parts of linear low-density polyethylene, 0.8 parts of fumed silica powder, and 0.45 parts of antioxidant;

[0091] The secondary inner layer material comprises the following components by weight: 23 parts of low-density polyethylene, 42 parts of metallocene polyethylene, 14.5 parts of linear low-density polyethylene, 4.5 parts of cooling masterbatch, and 0.45 parts of antioxidant;

[0092] The inner layer material comprises the following components by weight: 14 parts of low-density polyethylene, 45 parts of metallocene polyethylene, 32 parts of linear low-density polyethylene, 0.7 parts of antioxidant, 0.7 parts of light stabilizer, and 0.45 parts of antioxidant;

[0093] The particle size of the fumed silicon dioxide powder in the middle layer material is 40 nm;

[0094] The density of the low-density polyethylene in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is 0.920 g / cm 3 The density of metallocene polyethylene is 0.927 g / cm 3 The density of linear low-density polyethylene is 0.933 g / cm 3 ;

[0095] The antioxidant model in the outer layer material, sub-outer layer material, middle layer material, sub-inner layer material and inner layer material is antioxidant 4010NA; the light stabilizer hindered amine stabilizer in the outer layer material and inner layer material is light stabilizer 944; the antioxidant in the outer layer material and inner layer material is antioxidant 168.

[0096] Example 3

[0097] (1) Mixed calcination

[0098] Nano aluminum powder, nano alumina powder, neodymium sulfate and cesium tungstate are uniformly mixed in a mixer to obtain a mixed powder, and then the temperature is controlled to be 1400° C., and the mixed powder is calcined in a nitrogen atmosphere for 85 minutes. After the calcination is completed, a calcined mixed powder is obtained;

[0099] The mass ratio of the nano aluminum powder, nano alumina powder, neodymium sulfate and cesium tungstate is 225:80:3.5:30;

[0100] The particle size of the nano aluminum powder is 55 nm;

[0101] The nano alumina powder is β-alumina with a particle size of 147 nm.

[0102] (2) Amidation modification

[0103] The calcined mixed powder was mixed with ethylenediaminetetraacetic acid solution, and soaked at room temperature for 35 minutes. After the soaking, it was filtered, washed, and dried in a nitrogen atmosphere to obtain an acid-treated mixed powder. The acid-treated mixed powder was mixed with N,N-dimethylformamide, stirred to disperse it evenly, and then diethylenetriamine was added and stirred to completely dissolve it. Then, carbodiimide was added, the temperature was controlled to 79°C, and stirred for 185 minutes. After the stirring was completed, it was filtered, washed, and dried in a nitrogen atmosphere, and redispersed to a particle size of less than 150 nm to obtain an amidated modified mixed powder;

[0104] The mass ratio of the calcined mixed powder to the ethylenediaminetetraacetic acid solution is 10:80;

[0105] The concentration of the ethylenediaminetetraacetic acid solution is 0.8 mol / L;

[0106] The mass ratio of the acid-treated mixed powder, N,N-dimethylformamide, diethylenetriamine and carbodiimide is 55:675:80:1.1.

[0107] (3) Preparation of cooling masterbatch

[0108] The amidated modified mixed powder and fumed silica powder were fed into a mixer, and after being evenly mixed, linear low-density polyethylene, antioxidant and light stabilizer were added. The temperature was controlled at 178°C and the mixing time was 55 minutes. After the mixing was completed, extrusion granulation was performed to obtain a cooling masterbatch.

[0109] The mass ratio of the amidated modified mixed powder, fumed silica powder, linear low-density polyethylene, antioxidant, and light stabilizer is 16:5.5:195:1.1:1.1;

[0110] The particle size of the fumed silica powder is 40 nm;

[0111] The density of the linear low-density polyethylene is 0.933 g / cm 3 ;

[0112] The model of the antioxidant is antioxidant 168;

[0113] The light stabilizer is a hindered amine stabilizer, and the model is light stabilizer 944.

[0114] (4) Preparation of cooling greenhouse film

[0115] The outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material are mixed evenly respectively, and added into five extruders corresponding to the outer layer, the sub-outer layer, the middle layer, the sub-inner layer and the inner layer respectively, and the extrusion working temperature of the five extruders is set to 182°C, and melting, mixing and plasticizing are performed in sequence, and then the plasticized materials in the five extruders are squeezed into the die head of the same five-layer co-extrusion film blowing machine for fusion, and extruded in a tubular shape through the die mouth, and then blown, cooled and rolled to obtain a cooling shed film;

[0116] The structure of the cooling greenhouse film is an outer layer, a sub-outer layer, a middle layer, a sub-inner layer, and an inner layer from top to bottom. The thickness of the outer layer is 0.03mm, the thickness of the sub-outer layer is 0.025mm, the thickness of the middle layer is 0.04mm, the thickness of the sub-inner layer is 0.025mm, the thickness of the inner layer is 0.03mm, and the total thickness of the cooling greenhouse film is 0.15mm.

[0117] The outer layer material comprises the following components by weight: 16 parts of low-density polyethylene, 55 parts of metallocene polyethylene, 38 parts of linear low-density polyethylene, 0.9 parts of antioxidant, 0.9 parts of light stabilizer, and 0.55 parts of antioxidant;

[0118] The secondary outer layer material comprises the following components by weight: 27 parts of low-density polyethylene, 48 parts of metallocene polyethylene, 15.5 parts of linear low-density polyethylene, 5.5 parts of cooling masterbatch, and 0.55 parts of antioxidant;

[0119] The middle layer material comprises the following components by weight: 27 parts of low-density polyethylene, 48 parts of metallocene polyethylene, 15.5 parts of linear low-density polyethylene, 1.2 parts of fumed silica powder, and 0.55 parts of antioxidant;

[0120] The secondary inner layer material comprises the following components by weight: 27 parts of low-density polyethylene, 48 parts of metallocene polyethylene, 15.5 parts of linear low-density polyethylene, 5.5 parts of cooling masterbatch, and 0.55 parts of antioxidant;

[0121] The inner layer material comprises the following components by weight: 16 parts of low-density polyethylene, 55 parts of metallocene polyethylene, 38 parts of linear low-density polyethylene, 0.9 parts of antioxidant, 0.9 parts of light stabilizer, and 0.55 parts of antioxidant;

[0122] The particle size of the fumed silicon dioxide powder in the middle layer material is 40 nm;

[0123] The density of the low-density polyethylene in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is 0.920 g / cm 3 The density of metallocene polyethylene is 0.927 g / cm 3 The density of linear low-density polyethylene is 0.933 g / cm 3 ;

[0124] The antioxidant model in the outer layer material, sub-outer layer material, middle layer material, sub-inner layer material and inner layer material is antioxidant 4010NA; the light stabilizer hindered amine stabilizer in the outer layer material and inner layer material is light stabilizer 944; the antioxidant in the outer layer material and inner layer material is antioxidant 168.

[0125] Comparative Example 1

[0126] The difference from Example 1 is that the mixing and calcining step is changed to the following operation:

[0127] The nano aluminum powder and the nano alumina powder are mixed uniformly in a mixer to obtain a mixed powder, and then the temperature is controlled to be 1350° C., and the mixed powder is calcined in a nitrogen atmosphere for 90 minutes. After the calcination is completed, a calcined mixed powder is obtained;

[0128] The mass ratio of the nano aluminum powder to the nano alumina powder is 200:75;

[0129] The particle size of the nano aluminum powder is 55 nm;

[0130] The nano alumina powder is β-alumina with a particle size of 147nm;

[0131] The remaining steps are the same to prepare the film.

[0132] Comparative Example 2

[0133] The difference from Example 1 is that part of the operation in the amidation modification step is omitted and the step is changed to the following operation:

[0134] The calcined mixed powder was mixed with an ethylenediaminetetraacetic acid solution, and soaked at room temperature for 30 minutes. After the soaking, the mixed powder was filtered, washed, and dried in a nitrogen atmosphere to obtain an acid-treated mixed powder.

[0135] The mass ratio of the calcined mixed powder to the ethylenediaminetetraacetic acid solution is 10:75;

[0136] The obtained acid-treated mixed powder was used to prepare a cooling masterbatch while keeping the dosage unchanged, and the remaining steps were the same to prepare a film.

[0137] Test Example 1 Film Physical Properties Test

[0138] The cooling films prepared in Examples 1-3 and Comparative Examples 1-2 were tested for transverse tensile strength, longitudinal tensile strength, transverse elongation at break, and longitudinal elongation at break according to the method in GB / T1040.1-2006;

[0139] According to GB / T16578.2-2009, the Elmendorf method is used to test the transverse right-angle tear load and longitudinal right-angle tear load of the film;

[0140] According to the method in GB / T9639.1-2008, the drop impact strength of the film was tested;

[0141] The results are shown in Table 1.

[0142] Table 1

[0143]

[0144] In Example 1-3, nano aluminum powder, nano alumina powder, neodymium sulfate, and cesium tungstate are mixed and calcined, amidated and modified, and a cooling masterbatch is prepared to finally prepare a cooling greenhouse film. The prepared greenhouse film has excellent physical properties, and has high tensile strength, elongation at break, right-angle tear load, and dart drop impact strength.

[0145] In Comparative Example 1, only nano-aluminum powder and nano-alumina powder were mixed and calcined. Neodymium sulfate was lacking in the mixed calcined components, resulting in a decrease in the mechanical properties of the film, among which the tensile strength and elongation at break decreased more seriously, and the right-angle tear load and dart drop impact strength also decreased to a certain extent;

[0146] In Comparative Example 2, the subsequent step of immersing the calcined mixed powder in an ethylenediaminetetraacetic acid solution in the amidation modification is omitted, and the obtained acid-treated mixed powder is used to prepare a cooling masterbatch, and finally a greenhouse film is prepared, resulting in a decrease in the mechanical properties of the film, among which the right-angle tear load and the dart drop impact strength decrease more seriously, and the tensile strength and elongation at break also decrease to a certain extent.

[0147] Test Example 2 Film Cooling Performance Test

[0148] The cooling performance of the cooling films prepared in Examples 1-3 and Comparative Examples 1-2 was tested, and the test method was as follows:

[0149] The cooling film was placed in a sealed container, and both sides of the film were completely isolated. The inner and outer sides were completely sealed independent spaces, and the outer side of the greenhouse film was irradiated with simulated sunlight with an intensity of 100,000 LUX. The temperature of the environment on the outer side was controlled to be 45°C, and the temperature on the inner side was controlled to be room temperature 23°C. The outer side of the film was continuously irradiated, and the temperature of the inner side was tested at 0h, 2h, 6h, and 12h of irradiation. The results are shown in Table 2.

[0150] Table 2

[0151]

[0152] In Example 1-3, nano aluminum powder, nano alumina powder, neodymium sulfate, and cesium tungstate are mixed and calcined, amidated and modified, and a cooling masterbatch is prepared to finally prepare a cooling greenhouse film. The prepared greenhouse film has excellent cooling performance. In a long-term high temperature environment and light, the inner side of the film can still maintain a relatively low temperature, and the cooling effect can be effectively achieved;

[0153] In Comparative Example 1, only nano-aluminum powder and nano-alumina powder were mixed and calcined. The mixed calcined components lacked neodymium sulfate, which resulted in a decrease in the cooling effect of the film. In a long-term high-temperature environment and under light, the temperature inside the film increased to a large extent.

[0154] Comparative Example 2 omits the subsequent step of immersing the calcined mixed powder in ethylenediaminetetraacetic acid solution in the amidation modification, and uses the obtained acid-treated mixed powder to prepare the cooling masterbatch, which is finally used to prepare the greenhouse film, resulting in a decrease in the cooling effect of the film. Under long-term high temperature environment and light, the temperature on the inside of the film rises more seriously.

[0155] Test Example 3: Film Optical Performance Test

[0156] The cooling films prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests of average infrared blocking rate, average ultraviolet blocking rate, and average light transmittance. The test equipment was an LS182 ultraviolet infrared blocking rate and visible light transmittance tester. The results are shown in Table 3.

[0157] Table 3

[0158]

[0159] In Example 1-3, nano-aluminum powder, nano-aluminum oxide powder, neodymium sulfate, and cesium tungstate are mixed and calcined, amidated and modified, and a cooling masterbatch is prepared to finally prepare a cooling greenhouse film. The prepared greenhouse film has excellent optical properties. The film can maintain high infrared and ultraviolet blocking rates while maintaining high light transmittance;

[0160] In Comparative Example 1, only nano-aluminum powder and nano-alumina powder were mixed and calcined. Neodymium sulfate was lacking in the mixed calcined components, resulting in a decrease in the optical properties of the film, a certain degree of decrease in the infrared blocking rate and the ultraviolet blocking rate, and a greater degree of decrease in the light transmittance of the film;

[0161] Comparative Example 2 omits the subsequent step of immersing the calcined mixed powder in an ethylenediaminetetraacetic acid solution in the amidation modification, and uses the obtained acid-treated mixed powder to prepare a cooling masterbatch, which is finally used to prepare a greenhouse film, resulting in a decrease in the optical properties of the film, a significant decrease in the infrared blocking rate and the ultraviolet blocking rate, and a certain decrease in the light transmittance of the film.

[0162] Test Example 4: Film Optical Performance Uniformity Test

[0163] The uniformity of light transmittance and light reflectance of the cooling films prepared in Examples 1-3 and Comparative Examples 1-2 was tested as follows:

[0164] In the films prepared in Examples 1-3 and Comparative Examples 1-2, samples of 1000 mm×1000 mm were selected. In the samples of this specification, each area unit of 100 mm×100 mm was used as a test unit, as a test unit for testing transmittance and reflectance. 100 test units were tested for each sample. The extreme values ​​of the highest and lowest values ​​of the two test units in each sample were used as indicators of uniformity. The infrared blocking uniformity, ultraviolet blocking uniformity, and transmittance uniformity were tested respectively. The results are shown in Table 4.

[0165] The test was conducted using the LS182 UV / IR rejection and visible light transmittance tester.

[0166] Table 4

[0167]

[0168] In Example 1-3, nano aluminum powder, nano alumina powder, neodymium sulfate, and cesium tungstate are mixed and calcined, amidated and modified, and a cooling masterbatch is prepared to finally prepare a cooling greenhouse film. The uniformity of the optical properties of the prepared greenhouse film is good, whether it is the uniformity of infrared blocking and ultraviolet blocking, or the uniformity of light transmission, all can maintain a high level;

[0169] In Comparative Example 1, only nano-aluminum powder and nano-alumina powder were mixed and calcined. Neodymium sulfate was lacking in the mixed calcined components, and the uniformity of the optical properties of the obtained greenhouse film was poor, among which the light transmittance uniformity decreased more seriously, and the infrared blocking uniformity and ultraviolet blocking uniformity both decreased to a certain extent;

[0170] Comparative Example 2 omits the subsequent step of immersing the calcined mixed powder in an ethylenediaminetetraacetic acid solution in the amidation modification, and uses the obtained acid-treated mixed powder to prepare a cooling masterbatch. The uniformity of the optical properties of the resulting greenhouse film is poor, among which the uniformity of the infrared ray blocking and the ultraviolet ray blocking decreases more seriously, and the light transmittance uniformity decreases to a certain extent.

Claims

1. A method for preparing a cooling film for a greenhouse, characterized in that: The preparation method comprises mixing and calcining, amidation modification, preparing cooling masterbatch, and preparing cooling greenhouse film; The mixed calcination method comprises: mixing nano aluminum powder, nano alumina powder, neodymium sulfate and cesium tungstate in a mixer to obtain a mixed powder; then controlling the temperature to be 1300-1400° C., calcining the mixed powder in a nitrogen atmosphere for 85-100 minutes; and obtaining a calcined mixed powder after the calcination is completed; The mass ratio of the nano aluminum powder, nano alumina powder, neodymium sulfate and cesium tungstate is 175-225:70-80:2.5-3.5:20-30; The amidation modification method comprises: mixing the calcined mixed powder with an ethylenediaminetetraacetic acid solution, soaking the mixed powder at room temperature for 25-35 minutes, filtering, washing, and drying the mixed powder under a nitrogen atmosphere after the soaking is completed to obtain an acid-treated mixed powder, mixing the acid-treated mixed powder with N,N-dimethylformamide, stirring to make it dispersed evenly, then adding diethylenetriamine, stirring to make it completely dissolved, then adding carbodiimide, controlling the temperature to 77-79° C., stirring for 185-210 minutes, filtering, washing, drying, and re-dispersing the mixed powder under a nitrogen atmosphere after the stirring is completed to obtain an amidation-modified mixed powder; The mass ratio of the calcined mixed powder to the ethylenediaminetetraacetic acid solution is 10:70-80; The concentration of the ethylenediaminetetraacetic acid solution is 0.8-1.1 mol / L; The mass ratio of the acid-treated mixed powder, N,N-dimethylformamide, diethylenetriamine, and carbodiimide is 45-55:525-675:70-80:0.9-1.1; The method for preparing the cooling masterbatch is as follows: amidation modified mixed powder and fumed silica powder are fed into a mixer, linear low-density polyethylene, an antioxidant, and a light stabilizer are added after being evenly mixed, and mixing is performed; after mixing is completed, extrusion granulation is performed to obtain the cooling masterbatch; The mass ratio of the amidated modified mixed powder, fumed silica powder, linear low-density polyethylene, antioxidant, and light stabilizer is 13-16:4.5-5.5:175-195:0.9-1.1:0.9-1.1; The method for preparing the cooling greenhouse film comprises: uniformly mixing the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material respectively, adding them to five extruders corresponding to the outer layer, the sub-outer layer, the middle layer, the sub-inner layer and the inner layer respectively, melting, mixing and plasticizing them in sequence, and then squeezing the plasticized materials in the five extruders into the die head of the same five-layer co-extrusion film blowing machine for fusion, and extruding them in a tubular shape through the die mouth, and then blowing and molding, cooling and winding to obtain the cooling greenhouse film; The outer layer material comprises the following components by weight: 14-16 parts of low-density polyethylene, 45-55 parts of metallocene polyethylene, 32-38 parts of linear low-density polyethylene, 0.7-0.9 parts of antioxidant, 0.7-0.9 parts of light stabilizer, and 0.45-0.55 parts of antioxidant; The secondary outer layer material comprises the following components by weight: 23-27 parts of low-density polyethylene, 42-48 parts of metallocene polyethylene, 14.5-15.5 parts of linear low-density polyethylene, 4.5-5.5 parts of cooling masterbatch, and 0.45-0.55 parts of antioxidant; The middle layer material comprises the following components by weight: 23-27 parts of low-density polyethylene, 42-48 parts of metallocene polyethylene, 14.5-15.5 parts of linear low-density polyethylene, 0.8-1.2 parts of fumed silica powder, and 0.45-0.55 parts of antioxidant; The secondary inner layer material comprises the following components by weight: 23-27 parts of low-density polyethylene, 42-48 parts of metallocene polyethylene, 14.5-15.5 parts of linear low-density polyethylene, 4.5-5.5 parts of cooling masterbatch, and 0.45-0.55 parts of antioxidant; The inner layer material comprises the following components by weight: 14-16 parts of low-density polyethylene, 45-55 parts of metallocene polyethylene, 32-38 parts of linear low-density polyethylene, 0.7-0.9 parts of antioxidant, 0.7-0.9 parts of light stabilizer, and 0.45-0.55 parts of antioxidant.

2. The method for preparing a cooling film for a greenhouse according to claim 1, characterized in that: In the mixed calcination method, the particle size of the nano aluminum powder is 55 nm; the nano alumina powder is β-type alumina with a particle size of 147 nm.

3. The method for preparing a cooling film for a greenhouse according to claim 1, characterized in that: In the amidation modification method, the redispersion method is to redisperse until the particle size is less than 150 nm.

4. The method for preparing a cooling film for a greenhouse according to claim 1, characterized in that: In the method for preparing the cooling masterbatch, the particle size of the fumed silica powder is 40 nm; the density of the linear low-density polyethylene is 0.933 g / cm 3 ; The model of the antioxidant is antioxidant 168; the light stabilizer is hindered amine stabilizer, model is light stabilizer 944.

5. The method for preparing a cooling film for a greenhouse according to claim 1, characterized in that: In the method for preparing the cooling masterbatch, the mixing method is to control the temperature to be 172-178° C., and to perform mixing for 55-65 minutes.

6. The method for preparing a cooling film for a greenhouse according to claim 1, characterized in that: In the method for preparing the cooling greenhouse film, the extrusion working temperature is 177-182°C.

7. The method for preparing a cooling film for a greenhouse according to claim 1, characterized in that: In the method for preparing the cooling greenhouse film, the structure of the cooling greenhouse film is a five-layer structure from top to bottom, namely, an outer layer, a sub-outer layer, a middle layer, a sub-inner layer, and an inner layer. The thickness of the outer layer is 0.03 mm, the thickness of the sub-outer layer is 0.025 mm, the thickness of the middle layer is 0.04 mm, the thickness of the sub-inner layer is 0.025 mm, the thickness of the inner layer is 0.03 mm, and the total thickness of the cooling greenhouse film is 0.15 mm.

8. The method for preparing a cooling film for a greenhouse according to claim 1, characterized in that: In the method for preparing the cooling greenhouse film, the particle size of the fumed silica powder in the middle layer material is 40 nm; the density of the low-density polyethylene in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material, and the inner layer material is 0.920 g / cm 3 The density of metallocene polyethylene is 0.927 g / cm 3 The density of linear low-density polyethylene is 0.933 g / cm 3 ; The model of the antioxidant in the outer layer material, the sub-outer layer material, the middle layer material, the sub-inner layer material and the inner layer material is antioxidant 4010NA; the light stabilizer in the outer layer material and the inner layer material is hindered amine stabilizer, model is light stabilizer 944; the antioxidant in the outer layer material and the inner layer material is antioxidant 168.

Citation Information

Patent Citations

  • EDTA (Ethylenediamine Tetraacetic Acid) modified bacterial cellulose membrane adsorbent as well as preparation method and application thereof

    CN108554389A

  • Five-layer co-extruded high-strength transparent film special for vegetables and flowers and preparation method thereof

    CN110605890A